2018
DOI: 10.3847/2041-8213/aaf743
|View full text |Cite
|
Sign up to set email alerts
|

The Disk Substructures at High Angular Resolution Project (DSHARP). V. Interpreting ALMA Maps of Protoplanetary Disks in Terms of a Dust Model

Abstract: The Disk Substructures at High Angular Resolution Project (DSHARP) is the largest homogeneous high-resolution (∼0. 035, or ∼ 5 au) disk continuum imaging survey with ALMA so far. In the coming years, many more disks will be mapped with ALMA at similar resolution. Interpreting the results in terms of the properties and quantities of the emitting dusty material is, however, a very non-trivial task. This is in part due to the uncertainty in the dust opacities, an uncertainty which is not likely to be resolved any… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
417
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 329 publications
(428 citation statements)
references
References 76 publications
10
417
1
Order By: Relevance
“…Of course, as illustrated in Birnstiel et al (2018), different assumptions about the dust grain composition and structure will affect how multi-wavelength intensities are translated to grain sizes. For example, unlike the compact DSHARP grains, the β curves of highly porous grains are nearly flat as a function of a max (e.g., Kataoka et al 2014).…”
Section: Constraints On Dust Grain Sizesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, as illustrated in Birnstiel et al (2018), different assumptions about the dust grain composition and structure will affect how multi-wavelength intensities are translated to grain sizes. For example, unlike the compact DSHARP grains, the β curves of highly porous grains are nearly flat as a function of a max (e.g., Kataoka et al 2014).…”
Section: Constraints On Dust Grain Sizesmentioning
confidence: 99%
“…A comparison of the dust absorption opacity index β between 1.1 and 2.1 mm to the β nominal values derived for GM Aur. The β curves are computed as a function of amax and p using the "DSHARP dust opacities" fromBirnstiel et al (2018). From top to bottom, the dark gray horizontal lines show the β values from the best-fit GM Aur model at D67, D145, and B168, respectively.…”
mentioning
confidence: 99%
“…Other authors have also studied the inclusion of the scattering effects in the radiative transfer. For example, Birnstiel et al (2018) found an analytic solution for vertically isothermal slabs with the Eddington-Barbier approximation. Using their solution, Liu (2019) found spectral indices below of 2, consistent with the results discussed in this section.…”
Section: Spectral Indexmentioning
confidence: 99%
“…This solution was used by D' Alessio et al (2001) to obtain the source function S ν and integrate the radiative transfer equation in models of accretion disks around T Tauri stars. Recently, the Miyake solution was included in radiative transfer models of the complex substructures observed in dust continuum images with high angular resolution of disks from the DSHARP project (Birnstiel et al 2018). Liu (2019) also used the Miyake solution together with Monte Carlo simulations to explain the anomalous spectral indices reported in some optically thick protoplanetary disks.…”
Section: Introductionmentioning
confidence: 99%
“…Information obtained about the dusty material in disks from observations is, however, prone to uncertainties as well since it is based on several assumptions, such as the disk temperature (which is typically assumed to be 20 K but could vary depending on disk size; Hendler et al 2017), and the dust opacity. The dust opacity is the major source of uncertainty because it depends on the grain size and composition, which are unknown in protoplanetary disks (e.g., Birnstiel et al 2018). Nevertheless, when comparing millimeter-observations of protoplanetary disks with models of disk evolution, the same assumptions can be taken in order to facilitate the comparison and understand the effect of different crucial physical processes in the formation of planets, such as grain growth and drift.…”
Section: Introductionmentioning
confidence: 99%